INVENTORY OF TĀLAVAS FOREST PARK AND RECOMMENDATIONS FOR ITS MANAGEMENT - Volšteine, Linda; Pučkina, Irēna (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2018)
It is hard to imagine a modern city without parks or other green spaces. Park is not only a place for relaxing or regaining strangth, but also it is a place for local festivities, different sports and a meeting place for friends and families. For reasons mentioned above, it is important to properly manage forest parks and other green territories. Tālavas forest park is located in Alūksne and covers 8.1 hectares. As the popularity of this park grows, it is important to remove all dangerous elements of the forest park. As most of the forest park territory is covered with trees it is important to make sure that all the trees are in good shape. So visual evaluation of trees has been performed. During the study health of trees has been assessed and visual evaluation of trees has been performed. Tree trunk, crown and root quality have been assessed. Also height and diameter of trees were stated. Besides visual evaluation of trees,determination of tree species was performed.After evaluation of trees recommendations for forest park management was made.